First Report of the Root-Knot Nematode Meloidogyne enterolobii Parasitizing Plantain ( Musa spp ., AAB) in Nigeria - Olajide, Emmanuel Olorunfemi; Kolombia, Yao; Amah, Delphine; Couvreur, Marjolein; Swennen, Rony; Coyne, Dr, Daniel Leigh; Cortada, Laura; Bert, Wim (Plant disease, 2023)
Plantain ( spp., AAB), an important staple food in Africa with West Africa accounting for 32% of global production, is prone to numerous pests and diseases of which plant-parasitic nematodes are a key concern. This includes root-knot nematodes (RKN; spp.), which infect the roots, causing them to become galled, deformed and swollen. The nematode is considered a global threat to production of many important agricultural crops due to its extremely virulent and aggressive nature (Philbrick . 2020). In 2019, during a survey to identify the diversity of nematodes associated with spp. in Nigeria, RKN females (n = 13) were isolated from a heavily galled root (50-75% galling) from a single plantain cv. Agbagba ( ., AAB) plant in Onne, Rivers State, Nigeria (4°43'08.8"N 7°10'37.5"E). Genomic DNA was extracted from three females and processed individually using worm lysis buffer and proteinase K (Bert . 2008). The females were identified as based on Nad5 mtDNA (Janssen . 2016), with GenBank accession no. ON010028, ON010027, ON010026, and were 100% homologous to the sequences MW965454, KU372358 and KU372359 (Supplementary Figure S1). The sampled plant did not show any specific above-ground symptoms but swellings were apparent on the secondary and tertiary roots, which were associated with RKN females that were embedded in the root tissue. All the life stages were found clustered together in the root cortex, where they created necrotic brown-black lesions. A mean value of 2,604 ± 820 (mean ± standard deviation) males, eggs and second-stage juveniles (J2) were extracted from 5 g of root sub-samples (n = 6) using the Hussey and Barker (1973) NaOCl method. On average 39 females were hand-picked (n = 6) from 5 g fresh root. Pure cultures were established from single egg masses and maintained on RKN-susceptible tomato plants ( cv. Marmande). To conduct Koch's postulates, two-month old plantlets of plantain cv. Agbagba (n = 5) were inoculated with 8000 J2s and eggs (initial population) of pure cultures in 8 L pots in a screenhouse in Nigeria. Non-inoculated plantlets were included as negative controls. The nematode reproduction factor (RF = final density / initial population) and root damage symptoms were assessed 90 days post-inoculation. All the inoculated plantlets had similar galling symptoms and extensive necrosis as was observed in the field (Supplementary Figure S2), with an average RF = 25.9. No symptoms were observed on control plants. Adult females (n = 2) removed from the roots were identified as based on Nad5 mtDNA (ON532789, ON532790) confirming that plantain cv. Agbagba is a host of . In Nigeria, has been reported to be associated with four plant species belonging to four plant families: Euphorbiaceae (Oyetunde . 2022), Cucurbitaceae (Bello . 2020), Dioscoreaceae (Kolombia . 2016), and Solanaceae (dos Santos . 2019). To our knowledge, this is the first report of on a member of the Musaceae in Nigeria and globally the first report on plantain ( ., AAB). The impact of on plantain productivity has yet to be determined but given the RF value obtained in the pathogenicity test, plantain is a suitable host. This calls for a comprehensive RKN diversity study to evaluate the geographic spread of on this important staple food crop in West Africa.